What is LD in Special Needs Education? - Chia, Noel Kok Hwee (Journal of the American Academy of Special Education Professionals, 2012)
This article discusses the abbreviated term LD commonly used, misused and abused by those working in the field or special education in Singapore. The term has become so loosely used that it can mean almost anything, e.g., Learning Deficits, Learning Deficiencies, Learning Difficulties and the list can go on. Chia and Wong (2010) have argued an urgent need to make a clear distinction among the many different terms of LD used in the psycho-educational diagnostic evaluation and profiling before the whole issue becomes more confusing to parents with special needs children and professionals working in special education. The main purpose of this article is to clarify the term by categorizing LD into six different levels and what each level of LD represents in an attempt to avoid further confusion, misdiagnosis and provision of inappropriate treatment.